ROMPENDO O SILÊNCIO: a fragmentação identitária do negro americano retratada nas obras O olho mais azul e A cor púrpura. - MENDES, Danielle Gomes (2018)
The present study deals with an analysis of the identity fragmentation of American Negros discussed in two important African-American works, namely, The Bluest Eye, by Toni Morrison, and The Color Purple, by Alice Walker. This analysis intend to demonstrate how segregationist ideologies, inherited from colonialism and imperialism were responsible for the identity conflicts faced by black people, especially African-Americans, and how the sequels left by successive traumatic events that marked the history of Afrodescendants interferes directly on how they relate interpersonally and with the environment in which they live. Therefore, this research is based on the assumptions of postcolonial literary criticism and on studies about Identity, specifically regarding diasporic identity, especially, under the consideration of authors such as Frantz Fanon, Edward Said, Homi Bhabha, Bell Hooks, Kabengele Munanga, among others. Initially, a brief historical and literary contextualization regarding the postcolonial period will be presented, starting with the colonizing action of Europeans that led Europe to become a great power. Then the colonization of the North American territory will be discussed. The last topic of this moment will address European segregationist ideologies, and the new literature from ex-colonized peoples that emerged during this period. The following chapter will explain the identity fragmentation of the Black- American and its conflicts with the homeland, the origins, as well as the conflicts related to ethnic issues and their affective relations. Then, an overview on African-American literature will be drawn, highlighting the social movements in favor of the valorization of the black culture. Finally, will be presented an analysis of the literary works, which intend to show the neglectfulness and prejudice context that Black-Americans faced and how the experiences in this oppressive scenario were responsible for their identity conflicts. From the analysis, it is possible to perceive that the oppression context experienced by the black community influenced the way it perceives itself in the world, where the white supremacy reigns, interfered in its sense of belonging in respect to the homeland, as well as its capacity to love, and in how African- American literature is marked by such resentments.